Podoplanin immunoexpression in odontogenic lesions: a systematic review, meta-analysis, and integrated bioinformatic analysis - Alarcón-Sánchez, Mario Alberto; Luna-Bonilla, Getsemani; Romero-Servin, Selenne; Heboyan, Artak (Diagnostic pathology, 2024)
Background Podoplanin (PDPN) is a transmembrane glycoprotein implicated in the pathogenesis of odontogenic lesions (OL). It is localized at the membrane and cytoplasmic level, and its interaction with other proteins could trigger cell proliferation, invasion and migration. The main objective of this systematic review is to explore the immunoexpression pattern of podoplanin in OL. In addition, as secondary objectives, we aimed to compare the immunostaining intensity of PDPN in OL, to analyze its interaction networks by bioinformatic analysis and to highlight its importance as a potential diagnostic marker useful in the pathogenesis of OL. Methods The protocol was developed following PRISMA and Cochrane guidelines. The digital search was performed in the databases: PubMed/MEDLINE, ScienceDirect, Scopus, Web of Science and Google Schoolar from August 15, 2010 to June 15, 2023. We included cross-sectional and cohort studies that will analyze the pattern of PDPN immunoexpression in OL. Two investigators independently searched for eligible articles, selected titles and abstracts, analyzed full text, conducted data collection, and performed assessment of study quality and risk of bias. In addition, part of the results were summarized through a random-effects meta-analysis. STRING database was used for protein-protein interaction analysis. Results Twenty-nine relevant studies were included. The ages of the subjects ranged from 2 to 89 years, with a mean age of 33.41 years. Twenty-two point two percent were female, 21.4% were male, and in 56.4% the gender of the participants was not specified. A total of 1,337 OL samples were analyzed for PDPN immunoexpression pattern. Ninety-four (7.03%) were dental follicles and germs, 715 (53.47%) were odontogenic cysts, and 528 (39.49%) were odontogenic tumors. Meta-analysis indicated that the immunostaining intensity was significantly stronger in odontogenic keratocysts compared to dentigerous cysts (SMD=3.3(CI=1.85-4.82, p =0.000*). Furthermore, bioinformatic analysis revealed that PECAM-1, TNFRF10B, MSN, EZR and RDX interact directly with PDPN and their expression in OL was demonstrated. Conclusions The results of the present systematic review support the unique immunoexpression of PDPN as a potential useful diagnostic marker in the pathogenesis of OL.